2016
DOI: 10.1093/mnras/stw2563
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the Andromeda giant stream: asymmetric structure and disc progenitor

Abstract: We focus on the evidence of a past minor merger discovered in the halo of the Andromeda galaxy (M31). Previous N-body studies have enjoyed moderate success in producing the observed giant stellar stream (GSS) and stellar shells in M31's halo. The observed distribution of stars in the halo of M31 shows an asymmetric surface brightness profile across the GSS; however, the effect of the morphology of the progenitor galaxy on the internal structure of the GSS requires further investigation in theoretical studies. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 56 publications
2
59
2
Order By: Relevance
“…Thus, it is a relatively young feature. The spatial morphology of the stream, in particular the relatively well-defined northern edge and the "fanning" of material to the south, suggests that the progenitor might have been a disk galaxy (Fardal et al 2008;Kirihara et al 2017b). It is worth noting that the age of the stream is reasonably close to the age of the star forming ring in M31 Dalcanton et al 2012).…”
Section: A Census Of M31 Stellar Halo Substructurementioning
confidence: 75%
“…Thus, it is a relatively young feature. The spatial morphology of the stream, in particular the relatively well-defined northern edge and the "fanning" of material to the south, suggests that the progenitor might have been a disk galaxy (Fardal et al 2008;Kirihara et al 2017b). It is worth noting that the age of the stream is reasonably close to the age of the star forming ring in M31 Dalcanton et al 2012).…”
Section: A Census Of M31 Stellar Halo Substructurementioning
confidence: 75%
“…The similarity of the photometric metallicity and age distributions of stellar populations in the SE shelf and GSS (Brown et al 2003(Brown et al , 2006Gilbert et al 2007) further bolstered the hypothesis that the SE shelf and GSS were tidal debris from the same event. The prediction of the SE shelf illustrates that minor merger models for the formation of the GSS (M å ∼ (1 − 5) × 10 9 M e ; Fardal et al 2006Fardal et al , 2007Fardal et al , 2008Fardal et al , 2013Mori & Rich 2008;Kirihara et al 2014;Sadoun et al 2014;Kirihara et al 2017;Miki et al 2016) can successfully reproduce the broad morphological and kinematical features of the stream while accounting for diffuse shell-like features such as the Northeast (Ferguson et al 2002(Ferguson et al , 2005 and West (W; Fardal et al 2007) shelves as part of the forward continuation of the stream. In further support of this hypothesis, Fardal et al (2012) showed that the kinematics of the W shelf were strikingly similar to predictions for the feature and that the shelf's metallicity was consistent with that of the GSS.…”
Section: Introductionmentioning
confidence: 83%
“…Since this analysis does not consider the evolution of the tidal debris, a comprehensive survey by N-body simulations including the effects of a progenitor's morphology, a live disc and the density profile of the DMH is necessary for further analysis (cf. Mori & Rich 2008;Kirihara, Miki & Mori 2014;Miki, Mori & Rich 2016;Kirihara et al 2017).…”
Section: Summary and Discussionmentioning
confidence: 99%